PRELIMINARY STUDY ON POPULATION DYNAMIC OF HARPACTICOID COPEPOD Euterpina acutifrons IN CULTURE CONDITION - Philip Teguh Imanto; Gede S. Sumiarsa; Made Suastika (Indonesian Aquaculture Journal, 2007)
The most important factor to high mortality rate in larval rearing is feeding success in early larval stage related to kind and size of natural live food. Copepod basically is the main source of natural food in the open ocean having some advantages such as smaller size of nauplii, attractive movement and high nutritional value. Observation on population dynamic of harpacticoid copepod Euterpina acutifrons was carried out using 5-L plastic bucket with initial density 100 ind./L. Green algae Nannochloropsis sp. was added to culture media at density of 50,000 cells/mL as a basic feed and additional feeds given were wheat flour (group A) and chicken liver (group B) at a rate of 50 mg/bucket. The result showed that there was no difference on population pattern in both groups where the incubation time took eight days to hatch, from nauplii to the copepodite stage was three days and from copepodite to adult copepod took five-to-six days. The differences came up from population number: in group (A) the highest number of copepod-bearing-egg was only 133 ind., nauplii production up to 62,833 ind. and number of copepodites was 22,333 ind. lower compared to group (B) with the highest copepod-egg was 308 ind., nauplii was 113,333 ind. and copepodite was 51,167 ind. The conclusion pointed out that the kind of food did not influence population pattern (quality) but gave effect to population growth.